PENGARUH MOTIVASI DAN DISIPLIN TERHADAP PRODUKTIVITAS KERJA DI KANTOR DINAS SOSIAL KABUPATEN TORAJA UTARA - Felia Febronia; Dina Ramba; Jemi Pabisangan Tahirs (ITB AAS Indonesia Surakarta, 2026)
This study aims to examine the effect of motivation and discipline on employee work productivity at the Social Service Office of North Toraja Regency, both partially and simultaneously. This research used a quantitative method with a saturated sampling technique involving all 37 employees. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS. The results showed that motivation had a positive and significant effect on work productivity (t = 12.286; sig. < 0.001). Discipline also had a positive and significant effect on work productivity (t = 11.970; sig. < 0.001). Simultaneously, motivation and discipline significantly affected work productivity with a coefficient of determination (R²) of 0.907 or 90.7%.